Deciding to stay or go: Understanding the career intentions of women in the Australian mining industry - Nowak, Margaret; Marinelli, Mellisa; Lord, Linley; Bonner, D. (Edward Elgar Publishing, 2014)
Women seeking to develop careers paths in science and technology, engineering and mathematics fields (STEM occupations), areas characterised by an almost entirely male workforce, have been a focus of attention in research and discussions relating to gender equality in the workplace. While there have been increases in women’s representation in STEM careers, a challenge for management has been their retention. An important objective in seeking increased retention rates is to build a critical mass of women who can become role models for women who follow (Stout et al., 2011). In Australia there has been a focus on the attraction and retention of women in non-traditional occupations in the resources sector (Cabrera, 2006; Chamber of Minerals and Energy, 2008; Guillaume and Pochic, 2009; Barrera et al., 2010). Human resource (HR) practitioners have traditionally had remuneration and promotion, employee awards, and staff development in their armoury to reinforce commitment and reduce turnover. These focus on the external drivers and career success indicators and assume homogeneity amongst employees in career values and career motivation. Literature on women’s workforce experiences has been critical of the assumption that women can be encompassed by male centric models of motivation towards career success and advancement and workplace behaviour (Eagly and Karau, 2002; O’Neil et al., 2004; O’Neil and Bilimoria, 2005; O’Neil et al., 2008; Rudman and Phelan, 2008). An alternative approach to attraction and retention is to understand career values and drivers of individual employees and seek policies and career trajectories that take these into account.